Clonal Analysis of Peripheral Blood T Cells in patients with Hashimoto's Thyroiditis at Different Stages using TCR Sequencing - Yufeng Liu; Huachao Zhu; Qing Zhang; Yanru Zhao (Immunobiology)
Background: Hashimoto's Thyroiditis (HT) is a prevalent autoimmune disorder characterized by progressive thyroid damage mediated by T cells. The clonal diversity and expansion of T cells play a critical role in the pathogenesis of HT, but detailed insights into these characteristics at various disease stages are lacking. Objective: To analyze and compare the clonal diversity and T cell receptor (TCR) repertoire in peripheral blood T cells across different stages of Hashimoto's Thyroiditis using TCR sequencing. Methods: Peripheral blood samples from 19 HT patients at different disease stages and 4 healthy controls were collected. TCR sequencing was performed to assess T cell diversity and clonal expansion. Statistical analyses, including Shannon's entropy and Simpson's index, were employed to compare TCR diversity. Additionally, differential VJ gene usage and amino acid sequence diversity were analyzed. Results: The results revealed significant differences in TCR diversity between HT patients and healthy controls, with HT patients showing lower diversity. Notably, the frequency of hyperexpanded clones was higher in HT patients. Specific VJ genes exhibited differential usage patterns across disease stages, and a set of unique amino acid sequences was identified in each stage. Conclusion: TCR sequencing highlights distinct clonal T cell expansions and shifts in VJ gene usage in HT patients, providing insights into the immune mechanisms driving disease progression.